Menemukan Islam di Minahasa: Islamisasi dalam Jaringan Rempah Nusantara - Azis, Muhammad Nur Ichsan (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2023)
Islamization in Minahasa is an interesting discourse to study. Discussions on religion, Islam and Christianity, in Minahasa often collided with the axis and process of the spice trading network and political policies. Local power is one of the attractions for the formation of spice networks and religious development in several strategic areas, including Minahasa. This article attempts to reveal and analyze Islam in Minahasa through the Nusantara spice trading network. historical method; heuristics, criticism, interpretation, and historiography, are used in this article with a social science approach related to Islamization. Islamization in Minahasa developed through the arrival and existence of actors in the trade network such as sailors-traffickers, preachers, as well as various conditions that affected society in the religious relations that were formed. The Islamization of Minahasa is unique with the emergence of a Muslim community nucleus in the coastal and inland areas until the 20th century.